2000
DOI: 10.1073/pnas.250471997
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into the binding of cardiac glycosides to the digitalis receptor revealed by solid-state NMR

Abstract: Several biologically active derivatives of the cardiotonic steroid ouabain have been made containing NMR isotopes ( 13 C, 2 H, and 19 F) in the rhamnose sugar and steroid moieties, and examined at the digitalis receptor site of renal Na ؉ ͞K ؉ -ATPase by a combination of solid-state NMR methods. Deuterium NMR spectra of 2 H-labeled inhibitors revealed that the sugar group was only loosely associated with the binding site, whereas the steroid group was more constrained, probably because of hydrogen bonding to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
1
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 31 publications
(46 reference statements)
5
48
1
2
Order By: Relevance
“…Keenan et al [28] have postulated a model in which the lactone ring is located close to the extracellular space and the rhamnose is embedded deeply into the membrane. The latter orientation does not fit with earlier nuclear magnetic resonance studies showing that the rhamnose has a high mobility [29].…”
Section: Discussioncontrasting
confidence: 92%
“…Keenan et al [28] have postulated a model in which the lactone ring is located close to the extracellular space and the rhamnose is embedded deeply into the membrane. The latter orientation does not fit with earlier nuclear magnetic resonance studies showing that the rhamnose has a high mobility [29].…”
Section: Discussioncontrasting
confidence: 92%
“…Mutagenesis has identified residues in the outermost segments of TM1, TM2, TM4, TM5, TM6, and TM7, and their connecting loops, that influence apparent affinity of ouabain binding or action (14, 17, 23, 34-37). Although evidence for direct interaction of these residues with cardiotonic steroids is lacking, the consensus interpretation pictures the steroid docking on the Na͞K pump's external surface, interacting with many of the identified amino acids (14,(38)(39)(40). Identification of the conserved Thr atop TM6 (34) and neighboring residues in the TM5-TM6 hairpin loop (35) as key determinants of ouabain apparent affinity led to the suggestion that cardiotonic steroids might act by preventing motion of the TM5-TM6 hairpin loop, thereby impeding ion passage to or from the deeper binding sites between TM4, TM5, and TM6 (35).…”
Section: Discussionmentioning
confidence: 99%
“…The Li-salt of [U- 13 C, 15 N]ATP is obtained from Silantes (Munich, Germany) and Li-salts of unlabelled ATP and ADP are obtained from Sigma-Aldrich (Denmark).…”
Section: Methodsmentioning
confidence: 99%
“…Hence it was necessary to develop a strategy that enables peaks from bound nucleotide to be detected under these transient conditions. It is shown that measurements of 13 C isotropic chemical shift values provide preliminary information about the nucleotide binding sites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation